SmO thin films: a flexible route to correlated flat bands with nontrivial topology - Kasinathan, Deepa; Haverkort, Maurits W. (Arxiv, 2015)
Using density functional theory based calculations, we show that the correlated mixed-valent compound SmO is a 3D strongly topological semi-metal as a result of a 4
Gesehen am 24.11.2017